Possible Involvement of Monoaminergic Neurotransmission in Antidepressant‐like activity of Emblica officinalis Fruits in Mice - Dhingra, Dinesh (CNS Neurosci Ther, 2011)
Aims: In this study, antidepressant‐like activity of Emblica offcinalis Gaertn. fruits (Family: Euphorbiaceae) was evaluated in Swiss young male albino mice employing tail suspension test and forced swim test. Methods: Aqueous extract (200 and 400 mg/kg) of the fruits was administered orally for 14 successive days to mice. On day 14, 60 min after extract administration, animals were subjected to tail suspension test and forced swim test. Results: The extract significantly decreased immobility period in both tail suspension test and forced swim test, indicating significant antidepressant‐like activity. The lower dose (200 mg/kg) of the extract showed better antidepressant‐like action. The efficacy of the extract was found to be comparable to fluoxetine (20 mg/kg), imipramine (15 mg/kg), and phenelzine (20 mg/kg). The extract did not show any significant effect on locomotor activity of the mice. Prazosin (alpha(1)‐adrenoceptor antagonist), sulpiride (selective D(2)‐receptor antagonist), baclofen (GABA(B) agonist), and p‐CPA (tryptophan hydroxylase inhibitor) significantly attenuated the extract‐induced antidepressant‐like effect. The extract also significantly decreased brain MAO‐A levels. Discussion: The aqueous extract might produce antidepressant‐like effect by interaction with α(1)‐adrenoceptors, dopamine D(2)‐ receptors, serotonergic, and GABA(B) receptors. In this study, aqueous extract was found to contain 2.94% of ascorbic acid. So ascorbic acid and other constituents like flavanoids, tannoid principles, and polyphenolic substances present in the aqueous extract of E. officinalis might be responsible for its antidepressant‐like activity. Conclusions: Thus, aqueous extract of E. officinalis showed antidepressant‐like activity probably by inhibiting MAO‐A and GABA; and also due to its antioxidant activity.